Radikalisme untuk Kristenisasi: Reinterpretasi Amanat Agung Matius 28 : 16 – 20 dalam Penginjilan di Konteks Kemajemukan Agama dan Kepercayaan Masyarakat Indonesia - Elba Pranata Barus; Boby Andika Sinaga (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Indonesia, as a pluralistic nation, faces serious challenges related to religious radicalism, often triggered by a literal understanding of sacred texts, including the Great Commission in Matthew 28:16–20. This study emphasizes the need for reinterpretation of this text, not as a mandate for Christianization, but as a call to disciple others in the spirit of love and tolerance. The research method used is qualitative with a literature review, offering novelty through a contextual reinterpretation approach, different from previous studies that tended to be textual. This approach seeks to understand the text within the social and cultural context of pluralistic Indonesia, emphasizing values such as love, respect for pluralism, and honoring religious diversity. The findings show that this reinterpretation aligns with the values of Pancasila and can contribute to preventing the seeds of radicalism while strengthening interfaith harmony. By promoting inclusivity and peace, Christian mission can be a positive force in maintaining religious harmony in Indonesia. In conclusion, the Christian mission must shift from an exclusive paradigm focused on aggressive proselytization to a theocentric paradigm that embraces pluralism and promotes interfaith tolerance, to achieve peace amid the diversity of Indonesian society.